PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN PRESTASI BELAJAR IPA DI KELAS V SD NEGERI NO. 104607 SEI ROTAN T.A. 2019/2020 - Indri Guntari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2020)
This studies examines Improving Student Learning Outcomes in Science Subjects using the Experimental Method for class V of State Elementary School No.104607 Sei Rotan T.A 2019/2020. The method used is to give students the freedom to experiment by doing experiments on something, observing the process, and writing down the results of the experiment. Learning using the experimental method will train and teach students to carry out experiments by searching for and finding their own answers to the problems they face. The results of research and discussion show that student learning outcomes in science subjects in class V-B of SD N 104607 Sei Rotan on heat transfer material for the 2019/2020 academic year using experimental methods have increased. This is evident from the average score at pre-test of 54.77, increasing to 69.89 in cycle I and increasing to 86.59 in cycle II. Before the action was implemented, students' ability to solve questions was still low and had not been successful, namely 13 people or 29.55% who completed it. After taking action in cycle I, the level of learning completeness was obtained at 22 people or 50%, which means that overall the students had not reached the minimum standard of completeness. The test results in cycle II showed that the students' learning completeness level was 38 people or 86.36%, which means that overall the students had reached a minimum standard of completeness above 85%. This shows that there has been an increase in student learning outcomes from before to after the implementation of the experimental method in the science subject Heat Transfer in class V-B SD N 104607 Sei Rotan T.A 2019/2020.